2021
DOI: 10.1002/anie.202107253
|View full text |Cite
|
Sign up to set email alerts
|

Switchable, Reagent‐Controlled Diastereodivergent Photocatalytic Carbocyclisation of Imine‐Derived α‐Amino Radicals

Abstract: Ar eagent-controlled stereodivergent carbocyclisation of aryl aldimine-derived, photocatalytically generated, aamino radicals possessing adjacent conjugated alkenes,affording either bicyclic or tetracyclic products,i sd escribed. Under net reductive conditions using commercial Hantzsche ster,t he a-amino radical species underwent as ingle stereoselective cyclisation to give trans-configured amino-indane structures in good yield, whereas using as ubstituted Hantzsch ester as am ilder reductant afforded cis-fuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 134 publications
0
17
0
Order By: Relevance
“…In 2021, Hamlin and Dixon showed that the intramolecular cyclization of α-amino radicals generated from imines could be switched depending on the structure of the Hantzsch ester used as an additive (Scheme ). Note that the solvent was changed after the optimization to improve the reaction. When unsubstituted Hantzsch ester HE - 1 was added to compound 23 - 1 in the presence of an Ir photocatalyst, the five-membered ring was formed giving trans - 23 - 2 as the main product.…”
Section: Conditions-controlled Divergent Reactionsmentioning
confidence: 99%
“…In 2021, Hamlin and Dixon showed that the intramolecular cyclization of α-amino radicals generated from imines could be switched depending on the structure of the Hantzsch ester used as an additive (Scheme ). Note that the solvent was changed after the optimization to improve the reaction. When unsubstituted Hantzsch ester HE - 1 was added to compound 23 - 1 in the presence of an Ir photocatalyst, the five-membered ring was formed giving trans - 23 - 2 as the main product.…”
Section: Conditions-controlled Divergent Reactionsmentioning
confidence: 99%
“…This reaction also allowed exploration of one new kind of α-amino radical, which could be utilized in the preparation of tetrahydroquinolines. 17 Combined with the above three-component reaction, a divergent reaction strategy between secondary aniline, aldehyde, and vinyl sulfone appeared, resulting in the synthesis of an α-functionalized acyclic tertiary aniline and tetrahydroquinolines. However, because the yield of the ortho -alkenylation of the secondary aniline is low, here, we focused on the cyclization reaction between 2-vinylaniline and aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalysis has broad and fascinating application in the fields of energy conversion, environmental remediation, organic synthesis, and photodynamic therapy. In the process of photocatalytic reactions, in order to realize the series regulation of the catalyst reaction activity, pathway, rate, and product selectivity, a great number of efforts have been made, such as controlling the morphology and structure of the catalyst, regulating the reactive species, changing the reaction conditions, adding additives, and so on. Although numerous interesting and excellent studies have been reported successively in this regard, there are still great difficulties and challenges in its regulation because it involves a series of complex energy conversion, carrier transport, and surface reaction processes.…”
Section: Introductionmentioning
confidence: 99%